As dificuldades na aprendizagem da Matemática no ensino fundamental: desenvolvido com os professores do município de Capanema-PA - SILVA, Nádia Monteiro Santiago (2023)
Mathematics learning is fundamental for the cognitive development of students in elementary school, being a discipline that often presents challenges for both students and teachers. The objective of this research is to identify and analyze the main learning difficulties in mathematics in Elementary School faced by Mathematics teachers in the municipality of Capanema/PA, and to propose a pedagogical strategy to overcome these difficulties. The predominantly qualitative methodology with a bibliographical review to reflect on the studies and theories related to learning Mathematics at this level of education, a questionnaire was answered in the Google Forms.app application, containing 20 open questions that offered the Mathematics teacher to use their words to answer the questions. Based on the literature review and data analysis, teachers cited alternative teaching methods, differentiated teaching resources or training programs for teachers to provide improvements in teaching and learning in mathematics. As a result, we hope that the proposed pedagogical strategy developed can help teachers in teaching Mathematics, improving student learning and promoting a more effective teaching in this discipline.